AgriTech4Egypt Innovation Challenge Demo Day - Menza, Gianpiero; Zaccari, Claudia (2024)
AgriTech4Egypt Innovation Challenge 2024, Demo Day Presentation, including all Pitch Decks in pitching order. Demo Day celebrated the journey of 15 agri-tech innovation teams selected from a pool of over 900 global applicants, who have successfully completed an intensive 5-month acceleration program, combining business training and technical assistance, to transform Egyptian food systems.